2018
DOI: 10.1038/s41467-018-06809-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesopontine cholinergic inputs to midbrain dopamine neurons drive stress-induced depressive-like behaviors

Abstract: Stressful life events are primary environmental factors that markedly contribute to depression by triggering brain cellular maladaptations. Dysregulation of ventral tegmental area (VTA) dopamine neurons has been causally linked to the appearance of social withdrawal and anhedonia, two classical manifestations of depression. However, the relevant inputs that shape these dopamine signals remain largely unknown. We demonstrate that chronic social defeat (CSD) stress, a preclinical paradigm of depression, causes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Even though most of our examples of CAV and intersectional method applications concerned circuit anatomy, the same intersectional approaches can be easily tweaked for functional analyses or molecular profiling. For instance, a variety of effector molecules have been conditionally expressed for either chemogenetics (Boender et al, 2014;Augur et al, 2016;Alcaraz et al, 2018;Fernandez et al, 2018;Ramanathan et al, 2018;Kakava-Georgiadou et al, 2019), optogenetic (Eliava et al, 2016;Li et al, 2016), projection-specific genetic ablations (Wu et al, 2012;Liu et al, 2016), optical calcium imaging (Otis et al, 2017(Otis et al, , 2019, and molecular profiling (Ekstrand et al, 2014). Furthermore, the ability of CAV to seamlessly deliver and selectively express effectors can be paired with classical techniques, such as slice or in vivo electrophysiology (Eliava et al, 2016;Li et al, 2016), and a variety of behavior paradigms (Liu et al, 2016;Kakava-Georgiadou et al, 2019).…”
Section: Applicationsmentioning
confidence: 99%
“…Even though most of our examples of CAV and intersectional method applications concerned circuit anatomy, the same intersectional approaches can be easily tweaked for functional analyses or molecular profiling. For instance, a variety of effector molecules have been conditionally expressed for either chemogenetics (Boender et al, 2014;Augur et al, 2016;Alcaraz et al, 2018;Fernandez et al, 2018;Ramanathan et al, 2018;Kakava-Georgiadou et al, 2019), optogenetic (Eliava et al, 2016;Li et al, 2016), projection-specific genetic ablations (Wu et al, 2012;Liu et al, 2016), optical calcium imaging (Otis et al, 2017(Otis et al, , 2019, and molecular profiling (Ekstrand et al, 2014). Furthermore, the ability of CAV to seamlessly deliver and selectively express effectors can be paired with classical techniques, such as slice or in vivo electrophysiology (Eliava et al, 2016;Li et al, 2016), and a variety of behavior paradigms (Liu et al, 2016;Kakava-Georgiadou et al, 2019).…”
Section: Applicationsmentioning
confidence: 99%
“…This non-specificity occurred despite our using the same antibody as used by others e.g. 39,40 . For the following three reasons, however, we do not view this lack of specificity in the c-fos signal as a major concern for the main findings and interpretation of this paper, i.e., that variations in photostimulation input produce tunable changes in hypoglossal motor output in-vivo and they identify REM sleep specific suppression of net motor excitability and responsivity.…”
Section: Discussionmentioning
confidence: 88%
“…These sections were incubated in the primary antibodies for 24 hrs at 4 °C and in the secondary antibodies for 1 hr at room temperature. The anti-c-Fos antibody (ab190289) has been used and validated 39,40 .…”
Section: Study 2: Experiments Across Sleep and Awake Statesmentioning
confidence: 99%
“…Interestingly, while an earlier study suggested distinct populations of VTA neurons involved in encoding reinforcement and avoidance, with the LDT to VTA projection involved in positive encoding and a projection from the lateral habenula to the VTA regulating aversion (Lammel et al, 2012), a later optogenetic study revealed a role of the LDT in avoidance encoding to aversive doses of nicotine that involved activation of IPN-sourced GABAergic inputs directed to phenotypically-unidentified neurons of the LDT, which projected to the VTA (Wolfman et al, 2018). Further, while not strictly an aversion-inducing stimuli, social defeat stress was associated with hyperactivity of cholinergic and glutamatergic LDT neurons which projected to the VTA, however, further studies indicated that of the two cell types, only cholinergic neurons were involved in maladaptive responses to stress (Fernandez et al, 2018). Although caution in making conclusions was noted, stimulation of LDT cholinergic afferents to DA-VTA neurons was found to enhance the increase in firing noted upon an aversive, paw pinch stimulation (Dautan et al, 2016).…”
Section: Ldt-vta Inputsmentioning
confidence: 93%